Analisis Perbandingan Tingkat Kesehatan Bank Dengan Metode Risk Based Bank Rating Pada PT BPR Bank Kertiawan : Analisis Selama dan Setelah Pandemi Covid-19 (2020-2023) - Ariani, Ketut Gita; Julianto, I Putu (Universitas Pendidikan Ganesha, 2025)
The COVID-19 pandemic significantly impacted the stability of the banking sector, including People’s Credit Banks (BPR), which play a strategic role in supporting the local economy. This study aimed to analyse and compare the financial health of PT BPR Bank Kertiawan during and after the pandemic using the Risk Based Bank Rating (RBBR) method. The method consists of four aspects: risk profile, good corporate governance (GCG), earnings, and capital. The population of this study included all financial statements and GCG reports of BPR Bank Kertiawan, with a sample taken from the 2020–2023 reporting period. Secondary data were collected from the official website of BPR Bank Kertiawan. The Wilcoxon Signed Rank Test was applied to analyse the data. The findings reveal that there were significant differences in the bank’s health conditions before and after the pandemic, particularly in the risk profile (measured by NPL) and earnings (measured by ROA). However, no significant differences were found in the risk profile (measured by LDR), GCG, and capital (measured by CAR). These results indicate that while the pandemic affected credit risk and profitability, it did not have a substantial impact on liquidity, governance, or capital adequacy. Keywords: Bank Soundness, Risk Based Bank Rating (RBBR), RGEC, Pandemic